Absorption performance of CO2 in high concentrated [Bmim][Lys]-MDEA aqueous solution. (15th October 2016) - Fu, Dong; Zhang, Pan; Wang, LeMeng
Abstract: The absorption performance of CO2 in 1-butyl-3-methylimidazolium lysinate ([Bmim][Lys]) promoted N-methyldiethanolamine (MDEA) aqueous solution was investigated at the temperatures ranging from 303.2 K to 323.2 K. The mass fractions of MDEA and [Bmim][Lys] respectively ranged from 0.3 to 0.45 and 0.05 to 0.15. The viscosities of CO2 -unloaded and CO2 -loaded MDEA-[Bmim][Lys] aqueous solutions were measured and modeled. The influences of temperature and concentration on the absorption capacity of CO2 were determined. The effects of temperature, solution concentration and solution viscosity on the absorption rate were illustrated. Highlights: Viscosity of carbonated MDEA-[Bmim][Lys] aqueous solution was measured and modeled. Effects of temperature, concentration and CO2 loading on viscosity were demonstrated. Absorption capacity of CO2 in MDEA-[Bmim][Lys] aqueous solution were measured. Effects of temperature, concentration and viscosity on absorption rate were studied.